Cox Proportional Hazard Regression Analysis to Identify Factors Influencing Student Study Period: Analisis Regresi Cox Proportional Hazard untuk Mengidentifikasi Faktor-Faktor yang Memengaruhi Lama Studi Mahasiswa - Anggraira, Attilah Suci; Nirwana, Muhammad Bayu; Subanti, Sri (RADIANT: Journal of Applied, Social, and Education Studies, 2023)
The length of study is the time needed by students to complete their education, which is calculated from the time they enter school until they graduate. In general, a student is considered to graduate on time if he has studied for no more than four years. This study aims to identify the factors that influence the length of study of students using survival analysis with the Cox Proportional Hazard regression model. This study used data from 146 students who were randomly selected enrolled at Sebelas Maret University, Faculty of Mathematics and Natural Sciences, batch 2017 and 2018. The research variables consisted of nine predictor variables that were thought to influence student length of study. The nine factors are gender, major, GPA, university entrance, scholarship, part-time work, region of origin, organization, and committee. The results show that the following factors that significantly influence the length of study of students are majors and GPA. The results of this study have important benefits for higher education administrators and policy makers to develop strategies that can help students complete study programs on time.